PENGARUH KUALITAS PRODUK, PROMOSI DAN LAYANAN PURNA JUAL TERHADAP KEPUTUSAN PEMBELIAN MOBIL HONDA JAZZ (Studi Kasus pada Honda Semarang Center Semarang) - Ayu Haris Permatasari Putri; Handoyo Djoko Waluyo; Ngatno Ngatno (Universitas Diponegoro, 2015)
Industrial development in Indonesia has grown so fast and rapid. One of the industry that growing rapidly is automotive industry, especially car. Many brands of car that available on the market, then there is increasingly intense effort from car company to capture large market share from other company. At this time segment of cars that are in demand are segment of cars hatchback, especially Honda Jazz car that being a leader on hatchback segment. However the sales of Honda Jazz at Honda Semarang Center in 2009-2013 are fluctuated. If it’s not addressed it will be a threat to it’s dominance on hatchback segment.The purpose of this research was to determine the influences of product quality, promotion, and after sales service on purchase decision of Honda Jazz Car at Honda Semarang Center, Semarang. This research method is explanatory on 88 respondents with purposive technique sampling. With data collection through interview, questioners, and literature review. The analysis technique used was quantitative. Quantitative analysis using cross tabulation, validity, reliability, correlation coefficient, coefficient of determination, simple and multiple regression analysis, as well as the significance test (t test and F test) and helped by application SPSS 16.0 for Windows.The result of statistic analysis known the influences of partially between product quality on purchase decision is 21,6 %, promotion on purchase decision is 17,7 %, and after sales service on purchase decision is 31,5 %, the influences of simultaneously between product quality, promotion, and after sales service on purchase decision are 35,0 % whereas 65,0 % affected by other factors.From that results can be concluded product quality, promotion, and after sales service influenced to purchase decision partially and simultaneously. Based on these conclusion so advice can be given for the Honda Semarang Center Company are to notice the product quality with innovation periodically, doing exciting promotions and increase promotion frequency, and providing training on employee to perform after sales service.